Strategi Digital Public Relations Camille Beauty Melalui Tiktok @Camillebeauty_Official - Alviona, Tsabitha Yonisa; Leonardi, Aska (Universitas Al Azhar Indonesia, 2025)
ABSTRACT. Camille Beauty in 2019 was not well known by the public or TikTok users when creating content and was less popular. Therefore, researchers want to examine how Camille Beauty can rise and be recognized by TikTok users through digital media. This research method uses descriptive research with a qualitative approach. The data analysis method in this research is qualitative descriptive analysis, the researcher processes and presents the data that has been collected. The sources in this research were marketing managers, social media specialists, and H&R from Camille Beauty. The data collection method uses in-depth interviews and documentation. The key person in this research is Mrs. Rani who serves as a social media specialist at Camille Beauty. The information person in this research is Mr. Levian as the marketing manager of Camille Beauty. In testing the validity of this research, triangulation was used using source triangulation. The results of this research inform the following things, namely; (1). Camille Beauty uses digital media as a forum for communicating with consumers as a way of communicating with the public. (2). Using TikTok as a means of digital media is the best choice for Camille Beauty because Camille Beauty can get good information or responses. The results of this research show that the activities carried out by Camille Beauty through Tiktok @camillebeauty_official are successful in using digital media, because Camille Beauty can be well known by Tiktok users by always actively interacting with Tiktok users every day.